Transitional B Cells and TLR9 Responses Are Defective in Selective IgA Deficiency - Lemarquis, Andri L.; Einarsdottir, Helga K.; Kristjansdottir, Rakel N.; Jonsdottir, Ingileif; Ludviksson, Bjorn R. (Frontiers in Immunology, 2018)
Selective IgA deficiency (IgAD) is the most common primary antibody deficiency in the western world with affected individuals suffering from an increased burden of autoimmunity, atopic diseases and infections. It has been shown that IgAD B cells can be induced with germinal center mimicking reactions to produce IgA. However, IgA is most prevalent antibody in mucosal sites, where antigen independent responses are important. Much interest has recently focussed on the role of TLR9 in both naïve and mature B cell differentiation into IgA secreting plasma cells. Here, we analyse the phenotype and function of T and B cells in individuals with IgAD following IgA inducing CpG-TLR9 stimulations. The IgAD individuals had significantly lower numbers of transitional B cells (CD19+CD24hiCD38hi) and class switched memory B cells (CD20+CD27+IgD-) ex vivo. However, proportions of T cell populations ex vivo as well as in vitro induced T effector cells and T regulatory cells were comparable to healthy controls. After CpG stimulation the transitional B cell defect was further enhanced, especially within its B regulatory subset expressing IL-10. Finally, CpG stimulation failed to induce IgA production in IgAD individuals. Collectively, our results demonstrate a defect of the TLR9 responses in IgAD that leads to B cell dysregulation and decreased IgA production.